Cradle and all - Patterson, James, 1947- (New York : Warner Vision Books, 2001)
Anne Fitzgerald, a former nun turned private investigator, is hired by the Archdiocese of Boston to investigate two claims of immaculate conception in Boston and Ireland, and quickly comes to realize that both young women, and possibly the entire human race, are in grave danger.
Library Journal.
Publisher's Weekly.
Wilson's Fiction.
Library Journal, April 2000.
Publisher's Weekly, March 2000.
Wilson's Fiction, March 2006.
Keywords: Good and evil -- Fiction; Immaculate conception -- Fiction; Women Detectives -- Fiction; Good and evil -- Fiction; Immaculate conception -- Fiction; Mystery fiction; Women Detectives -- Fiction; Boston (Mass.) -- Fiction; Ireland -- Fiction; Boston (Mass.) -- Fiction; Ireland -- Fiction; Mystery fiction